Functional characterization of bovine TIRAP and MyD88 in mediating bacterial lipopolysaccharide-induced endothelial NF-κB activation and apoptosis - Cates, Elizabeth A. (2008)
Mastitis is a prevalent disease in dairy cows. Gram-negative bacteria, which express the pro-inflammatory molecule lipopolysaccharide (LPS), are responsible for the majority of acute clinical cases of mastitis. Previous studies have identified differential susceptibility of human and bovine endothelial cells (EC) to the pro-inflammatory and injury-inducing effects of LPS. The Toll-like receptor (TLR)-4 signaling pathway, which is activated by LPS, has been well studied in humans, but not in ruminants. Human myeloid differentiation-factor 88 (MyD88) and TIR-domain containing adaptor protein (TIRAP) are critical proteins in the LPS-induced NF-κB and apoptotic signaling pathways. To assess the role of the bovine orthologs of these proteins in bovine TLR-4 signaling, dominant-negative constructs were expressed in bovine EC, and LPS-induced NF-κB activation and apoptosis evaluated. The results from this study indicate that bovine MyD88 and TIRAP play functional roles in transducing LPS signaling from TLR-4 to downstream effector molecules involved in NF-κB activation, and that TIRAP promotes apoptotic signaling.